Educating social values among future teachers of preschool education: criteria and indicators - Kapustina, O. (Problems of Engineer-Pedagogical Education, 2021)
The article is devoted to the process of upbringing as an effective means of training preschool education specialists, highlights the relevance and importance of promoting values, including social ones, in the educational process at higher education institutions and determines the role of pedagogical assessment in identifying the state of the development of social values among future teachers of preschool education. The basic principles of pedagogical assessment are highlighted. Emphasis is placed on the use of a qualimetric approach during the evaluation procedure, which is a quantitative assessment of the quality of an object and is widely used to measure pedagogical phenomena. The article offers examples of applying qualimetric models for determining the level of professional competence of pedagogical workers and assessing administrative processes in general secondary education institutions as well as professional activity of life safety teachers. It is concluded that it is necessary to develop clear criteria and indicators that are subject to measurement and reflect the specifics of research on the upbringing of future professionals in the field of preschool education. An analysis of scientific and pedagogical literature to determine the criteria and indicators of education of future teachers was conducted. The essence of the concepts “criterion” and “indicator” is analyzed. It was determined that most researchers understand the criterion as the basis for classification, which is a means of assessing pedagogical phenomena, a certain feature, and the indicator is interpreted as a characteristic of a certain criterion that can be directly measured. Based on the review of the scientific and pedagogical literature, criteria and indicators of the development of social values among the future of preschool teachers are proposed, which includes motivationoriented (motivation to develop one’s own social values; understanding of the necessity of promoting social values among future preschool teachers; motivation of future preschool teachers to promote social values (kidness, truth, justice)); professional and cognitive (knowledge of social values and ability to manifest them in life and pedagogical situations, knowledge of the content, structure of social values, ability to promote social values among preschool children); reflective and value-oriented (desire for self-education in terms of social values; self-analysis of one’s own social values; ability to regulate behavior based on social values).